ANALISIS FAKTOR AUDIT INTERNAL DAN PENGARUHNYA TERHADAP PELAKSANAAN GOOD CORPORATE GOVERNANCE - Gusnardi Gusnardi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2008)
To implement the good corporate governance as it was expected, especially in the BUMN Tbk. in Indonesia, it is important to optimize the role of internal audit. The purpose of this research is to explore the influence of internal audit partly and simultaneously on the good corporate governance at the state-owned companies (BUMN Tbk) in Indonesia.The data used in this research were primary data collected by questionnaires. The data analysis for hypothesis testing was the path analysis. This research done with research method of census by 13 at the state-owned companies (BUMN Tbk.) in Indonesia. The data used in this research were primary data collected by questionnaires. Result of this research indicates that audit factors partly and simultaneously has influenced significantly to exercise on the good corporate governance at the state-owned companies (BUMN Tbk.) in Indonesia.